[6+3] cycloaddition of fulvenes with 3-oxidopyrylium betaine: a novel methodology for the synthesis of fused cyclooctanoid natural products - Radhakrishnan, K. V.; Krishnan, K. Syam; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Tetrahedron Letters, 2005)
Fulvenes undergo an easy [6+3] cycloaddition with 3-oxidopyrylium betaines leading to 5-8 fused oxabridged cyclooetanoids. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cyclooctanoids; fulvenes; oxidopyrylium betaines; [6+3] cycloaddition

First enantiospecific synthesis of (+)-beta-herbertenol - Chavan, Subhash P.; Thakkar, M.; Kharul, Rajendra K.; Pathak, A. B.; Bhosekar, Gaurav V.; Bhadbhade, Mohan M. (Tetrahedron, 2005)
The first enantiospecific synthesis of (+)-beta-herbertenol, from naturally occurring R-(+)-citronellal, employing Taber's diazo decomposition protocol as the key step, is described. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: citronellal; diazo decomposition; enantiospecific

Identical molecular strings woven differently by intermolecular interactions in dimorphs of myo-inositol 1,3,5-orthobenzoate - Bhosekar, Gaurav V.; Murali, Chebrolu; Gonnade, Rajesh G.; Shashidhar, M. S.; Bhadbhade, Mohan M. (Crystal Growth & Design, 2005)
myo-Inositol 1,3,5-orthobenzoate exhibits polymorphic behavior depending upon the solvent and time allowed for crystallization. Long plates (form I, monoclinic P2(1)/n) are produced on crystallization from methanol, while crystallization from ethyl acetate mostly yielded squarish plates (form II, monoclinic P2(1)/c). The latter could also be obtained by achieving rapid nucleation from a supersaturated solution of methanol. Remarkably, the overall conformation of the individual molecules is very similar in both polymorphs, although free rotations were possible for the phenyl ring and for the three O-H groups. O-H center dot center dot center dot O linked one-dimensional isostructural molecular strings in the two forms weave differently by weak intermolecular interactions to produce the dimorphs. Striking difference is seen in the ``zipping'' of molecular layers via phenyl center dot center dot center dot phenyl contacts; thermodynamic crystals of form I utilize a well-recognized ``edge-to-face'' herringbone pattern, making C-H center dot center dot center dot pi interactions, whereas the kinetic crystals of form II show rather uncommon ``edge-to-edge'' organization, which makes short Ph-H center dot center dot center dot H-Ph contacts.

Synthesis and intramolecular nitrile oxide cycloaddition of 3,5 `-ether-linked pseudooligosaccharide derivatives: an approach to chiral macrooxacycles - Sengupta, J.; Mukhopadhyay, R.; Bhattacharjya, A.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V. (Journal of Organic Chemistry, 2005)
[GRAPHIC] 3,5'-Ether-linked pseudooligopentose derivatives were synthesized for the first time from readily available carbohydrate precursors. The 1,2-isopropylidene-protected ether-linked oligopentoses are potentially important as precursors of novel RNA analogues. Intramolecular cycloaddition of the nitrile oxides prepared from these derivatives led to the diastereoselective formation of chiral isoxazolines fused to 10-16-membered oxacycles. The stereochemistry of some of these isoxazolines was established by X-ray diffraction and NOESY analysis.

[6+3] cycloaddition of pentafulvenes with 3-oxidopyrylium betaine: a novel methodology toward the synthesis of 5-8 fused oxabridged cyclooctanoids - Krishnan, K. Syam; Sajisha, V. S.; Anas, S.; Suresh, C. H.; Bhadbhade, Mohan M.; Bhosekar, Gaurav V.; Radhakrishnan, K. V. (Tetrahedron, 2006)
Pentafulvenes undergo a facile [6+3] cycloaddition with 3-oxidopyrylium betaine, generated from the corresponding pyranulose acetate, leading to the formation of 5-8 fused oxabridged cyclooctanoids. The product is formed by a [6+3] cycloaddition, followed by a 1,5-hydrogen shift of the initially formed [6+3] adduct. The reaction was found to be general and a number of fulvenes with a wide range of substituents at the exocyclic double bond, that is, at the C6 position followed a similar reactivity pattern. The [6+3] adduct, a 5-8 fused oxabridged cyclooctanoid, is potentially amenable to a number of synthetic transformations due to the presence of an alpha, beta-unsaturated ketone and cyclopentadiene part. By selecting appropriately substituted fulvene and pyranulose acetates, it is possible to use this methodology for the synthesis of a wide range of 5-8 fused cyclooctanoids. The experimental results have been rationalized on the basis of theoretical calculations. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: fulvenes; oxabridged cyclooctanoids; oxidopyrylium betaine; [6+3] cycloaddition